Transformational Leadership in Adopting Online Learning - Gikonyo, Naomi; Ndiritu, Anne (University of Nairobi, 2021)
More than 1.725 billion learners across the globe are currently affected due to the closure of their learning institutions in response to the COVID-19 pandemic (UNICEF June 2020). Over 98% of the world's student population have found themselves out of school due to the COVID-19 outbreak. This population includes university students who were aspiring to complete their academic years. Schools and colleges are making every effort to ensure that teaching and learning are going on even during lockdown occasioned by COVID-19. Examples of postponed examinations include Cambridge International Examination and Kenya National Examinations. The closure of learning institutions has impacted not only the students but also the teachers and school leaders. In response to school closures, the use of online, e-learning and distance learning platforms have remained a key option available for the continuation of learning. Until the COVID-19 pandemic threatened university education, adoption of distance education and in particular, online learning in public universities in Kenya, has been very slow. Online learning provides access to higher education without physical contact in response to the COVID- 19 crisis.
Keywords: Kenya; Online Learning